Localization of sustainable development goals among non-teaching staff in higher education: the status quo dynamics at great Zimbabwe university - Nyambiya, Isaac; Chapungu, Lazarus; Maoela, Malebajoa Anicia (Frontiers in Education, 2024)
The influence of non-teaching staff on localising Sustainable Development Goals (SDGs) within universities is underexplored despite its potential significance. This study examines the familiarisation with SDGs at Great Zimbabwe University (GZU) using a mixed-methods research design, specifically the triangulation convergence model. We conducted a questionnaire survey with 70 randomly selected non-teaching staff from diverse departments and key informant interviews with purposively selected non-teaching staff. For additional details on SDGs localisation initiatives, secondary data sources were obtained from the information department and the university website. The results indicate that the non-teaching staff members at GZU exhibit a moderate familiarity with SDGs, scoring 42.14%. About 42.86% of the employees had engaged with SDGs documents. Interestingly, respondents perceived the institution as well-prepared for SDGs localisation, scoring 62.17%. The overall SDGs localisation score is 58.5%, with variations between specific SDGs. In particular, SDG 5 (Gender Equality) scores highest, while SDG 14 (Life below Water) is the least localised. The study identifies several obstacles that hinder nonteaching staff from actively contributing to SDG implementation, such as primarily financial constraints followed by lack of awareness, demotivated employees, insufficient training, and a scarcity of SDG materials. Structural challenges within the institution were also observed. To address these issues, the study underscores the need for management to play an enabling role and designate focal persons for SDGs to oversee project execution. Overall, this research sheds light on the current status of SDGs familiarisation in higher learning institutions and offers insights for enhancing the involvement of non-teaching staff in achieving SDG targets.